Ag/RGO Photocatalyst for Methyl Orange Treatment - Wai, Hong Mun; Noramirulikram, Abdul Halim; Fatema, Khatun; Azrina, Abd Aziz (Trans Tech Publications, 2022)
In present study, a simple chemical method for the synthesis of silver-reduced graphene oxide (AG/RGO) nanocomposite was reported. The objective is to evaluate the performance of AG/RGO in photocatalytic degradation activity of methyl orange (MO) under artificial visible light source. The synthesized catalyst was then characterized using field emissions scanning electron microscope with energy dispersive X-Ray spectroscope (FESEM-EDX), photoluminescence spectroscopy (PL) and UV-visible spectroscope (UV-VIS) to determine the morphology, physical and chemical composition of the photocatalyst. The characterization results show the synthesized catalyst possess nanometre dimension silver nanoparticles (AgNPs) were deposited on reduced graphene oxide sheets. The photocatalytic activity of 0.3 g AG/RGO obtained through the degradation of 5 mg/l MO is 93.74% with a degradation rate of 3.1 × 10-2 min-1.